PENDIDIKAN ISLAM PADA MASA DAULAH BANI UMAYYAH - Yusnadi Yusnadi; Fakhrurrazi Fakhrurrazi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
The history of Islamic education is in essence very closely related to the history of Islam. The period of Islamic education is always in the period of Islamic history itself. Islamic education at the time of the Prophet Muhammad SAW was a period of fostering Islamic education by cultivating Islamic education in everyday life in accordance with the teachings of the Qur'an. education in the period of the Umayyads had evolved when viewed from the aspect of its teaching, even though the system was still the same as in the time of the Prophet and the khulafaurrasyidin.